New Functions of Angiogenic Peptides in Osteoarthritic Cartilage - Mentlein, Rolf; Pufe, Thomas (Current Rheumatology Reviews, 2005)
Inflammation is often associated with angiogenesis and angiogenic peptides might also be involved in inflammatory diseases like osteoarthritis (OA). This review summarizes recent findings about the occurrence and function of vascular endothelial growth factor (VEGF) and another angiogenic / growth factor, pleiotrophin (PTN) in osteoarthritic cartilage. Both peptides are produced in OA chondrocytes, but not in normal adult chondrocytes. Beside their well known effects on the infiltration of blood vessels that are sometimes observed in OA, they have additional, auto-/paracrine effects on chondrocytes and osteoblasts of the subchondral bone. PTN is found in early stages of OA, and appears to be a protective factor inducing remodelling and chondrogenesis. VEGF is induced by mechanical overload and appears to increase OA progression. VEGF promotes cartilage remodelling by inducing matrix metalloproteinases and reducing their inhibitors. Under chronic inflammatory conditions, this should result in subsequent destructive processes in OA cartilage. Chemotactic effects of VEGF and PTN on osteoblasts and endothelial cells may contribute to additional pathologic features such as osteophyte formation and blood vessel invasion. Overall, angiogenic peptides are new autocrine factors in OA initiating cartilage remodelling. VEGF appears to contribute to destructive processes in late OA stages whereas PTN may play protective roles in earlier OA stages.
Keywords: metalloproteinases